2012
DOI: 10.1007/s10997-012-9228-3
|View full text |Cite
|
Sign up to set email alerts
|

Interlocking directorships and firm performance in highly regulated sectors: the moderating impact of board diversity

Abstract: 1 We should like to express our gratitude to ESRC for funding this research under grant number RES: 062-23-0782 (2008-2011) and to our colleague, Tim Miller, for his skilful assistance during the data processing stage. Interlocking directorships and firm performance… 2Interlocking directorships and firm performance in the highly regulated sectors: The moderating impact of board diversity ABSTRACTInterlocking directorships are a pervasive element of the corporate landscape. Academic literature documents many e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 107 publications
(147 reference statements)
5
88
1
3
Order By: Relevance
“…For instance, Fahlenbrach (2009) analysed a 10-year data investigating the relationship and reported that CEO ownership has negative impact on firm performance as measured by Tobin's q. Also, Kaczmarek et al (2014) examined the impact of CEO ownership in an attempt to find the effect of interlocking directorship. The study revealed that there is a significant negative relationship between CEO ownership and firm performance.…”
Section: Ceo Ownershipmentioning
confidence: 99%
“…For instance, Fahlenbrach (2009) analysed a 10-year data investigating the relationship and reported that CEO ownership has negative impact on firm performance as measured by Tobin's q. Also, Kaczmarek et al (2014) examined the impact of CEO ownership in an attempt to find the effect of interlocking directorship. The study revealed that there is a significant negative relationship between CEO ownership and firm performance.…”
Section: Ceo Ownershipmentioning
confidence: 99%
“…These external connections, by their very nature, increase the status and influence of networked team members. Further, there is evidence that interlinked directors who are in the numeric minority (i.e., women) are particularly influential as these directors are likely to have experience successfully articulating minority viewpoints in ways that increase the receptivity of other board members thereby granting them greater influence over firm strategy (Carpenter and Westphal, 2001;Kaczmarek et al, 2014;Shropshire, 2010;Westphal and Milton, 2000).…”
Section: Predictor Variablesmentioning
confidence: 99%
“…Final sample 178 191 191 the perceived human capital of the board of directors (see e.g., Kaczmarek et al 2014). We use Non-diversifying acquisitions and International acquisitions as proxies for a firm's acquisition strategy.…”
Section: Dependent Variables: Firm Performance and Acquisition Strategymentioning
confidence: 99%